2016
DOI: 10.1002/dev.21453
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of early environmental interventions on structural plasticity of the axon initial segment in neocortex

Abstract: Plasticity of the axon initial segment (AIS) is a newly discovered type of structural plasticity that regulates cell excitability. AIS plasticity has been reported to happen during normal development of neocortex and also in a few pathological conditions involving disruption of the inhibition/excitation balance. Here we report on the impact of early environmental interventions on structural plasticity of AIS in the mouse neocortex. C57BL/6 mice were raised

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…Our data adds to the literature by showing that brief exposure to MK-801 on the second week of life is enough to induce changes in GABAergic transmission as early as P21-28. This is consistent with increasing evidence supporting that postnatal NMDA antagonism during periods of rapid synaptogenesis significantly affects development of inhibitory transmission (Abekawa et al, 2007;Gu et al, 2016;Jones et al, 2014;Nozari et al, 2017;Roux et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our data adds to the literature by showing that brief exposure to MK-801 on the second week of life is enough to induce changes in GABAergic transmission as early as P21-28. This is consistent with increasing evidence supporting that postnatal NMDA antagonism during periods of rapid synaptogenesis significantly affects development of inhibitory transmission (Abekawa et al, 2007;Gu et al, 2016;Jones et al, 2014;Nozari et al, 2017;Roux et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Also, rapid dendritic growth is related with maturity of glutamatergic and GABA-ergic receptors (257, 258), making dendritic differentiation more prone to environmental influences. As such, for the development of early maturing neurons, as is the case for L3N, already during the perinatal and early postnatal period, the environment has an important role in regulating their morphological differentiation (259263).…”
Section: Sequential Differentiation Of Principal Neurons In the Prefrmentioning
confidence: 99%
“…To explain the results in the hippocampus, it was suggested that the increase of the AIS length of Ube3a model mice might reflect a homeostatic response to a reduction in neuronal excitability, driven by the increase of α1-NaKA expression ( Kaphzan et al, 2011 , 2013 ). It has been well established that the AIS is a dynamic structure, and that the expression of sodium channels can depend on input activity ( Grubb and Burrone, 2010 ; Kuba et al, 2010 , 2014 , 2015 ; Gutzmann et al, 2014 ; Nozari et al, 2017 ). It is remarkable that the increase in AIS length was associated with a more negative membrane potential, both at hippocampal CA1 pyramidal neurons ( Kaphzan et al, 2011 ) and in the present study, since a chronic depolarization induces a rapid change in AIS length in cultured neurons ( Evans et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%